Vertical location of ephemeral resources by adult Diptera: Implications for the colonization of cadavers in high-rise buildings. (July 2021) - Oliveira, D.L.; Vasconcelos, S.D.
Highlights: Necrophagous flies vary in their ability to reach baits exposed at different heights above ground. Calliphorids, Muscids and Sarcophagids were most captured closer to the ground. Phorids were most abundant between 11 and 29 m high. Calliphorids and Muscids can reach baits up to 48 m high. Sarcophagids and Phorids can reach traps from 67 to 85 m high. Graphical Abstract: ga1 Abstract: Sarcosaprophagous flies (Diptera) rank among the most common insects associated with human-transformed environments all over the world. Synanthropic species of the families Calliphoridae, Muscidae, Sarcophagidae and Phoridae, in particular, have tremendous forensic importance due to their ability to colonize human cadavers and thus provide information on minimum post-mortem interval. Recently, cases of flies colonizing cadavers inside buildings of different heights drew attention to the vertical dispersal abilities of these flies, a subject that has received little attention. We investigated the vertical distribution of sarcosaprophagous flies in an urban environment, using uninhabited buildings as experimental models in Northeastern Brazil. To assess the vertical stratification of flies, one in every three floors of nine buildings was sampled using traps baited with bovine spleen, from the ground to the 27th floor. Calliphoridae was the most abundant family (52.9%), followed by Muscidae (41.2%), Sarcophagidae (3.2%) and Phoridae (2.7%). Most of the insects were collected at ground level (78.8%), with a decreasing abundance registered on the higher floors. Nevertheless, adults of the four families tested here were able to reach substrates as high as the 15th floor, which corresponds to approximately 48 m in height. Regarding calliphorids, seven species were identified, of which Chrysomya albiceps (30.4%) and C. megacephala (68.3%) were the most abundant. This is, to our knowledge, the first detailed, replicated study on vertical resource localization of sarcosaprophagous flies.